2020
DOI: 10.1038/s41419-020-03279-y
|View full text |Cite
|
Sign up to set email alerts
|

JmjC-KDMs KDM3A and KDM6B modulate radioresistance under hypoxic conditions in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC), the most frequent esophageal cancer (EC) subtype, entails dismal prognosis. Hypoxia, a common feature of advanced ESCC, is involved in resistance to radiotherapy (RT). RT response in hypoxia might be modulated through epigenetic mechanisms, constituting novel targets to improve patient outcome. Post-translational methylation in histone can be partially modulated by histone lysine demethylases (KDMs), which specifically removes methyl groups in certain lysine residues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 51 publications
(68 reference statements)
3
28
0
Order By: Relevance
“…Additionally, this was further demonstrated in vivo, with reduced tumor size and angiogenesis, evaluated both macroscopically and histologically. We again highlight the versatility of the CAM assay for assessing tumor properties and response to drugs in vivo [61], also recently demonstrated for GCTs as well [62,63]. Interestingly, VIRMA knockdown resulted in significant protein expression decrease of all members of the methyltransferase complex (METTL3, the only component with catalytic activity; METTL14, which is relevant for substrate recognition, specificity and activity; and WTAP, which stabilizes the complex).…”
Section: Discussionsupporting
confidence: 58%
“…Additionally, this was further demonstrated in vivo, with reduced tumor size and angiogenesis, evaluated both macroscopically and histologically. We again highlight the versatility of the CAM assay for assessing tumor properties and response to drugs in vivo [61], also recently demonstrated for GCTs as well [62,63]. Interestingly, VIRMA knockdown resulted in significant protein expression decrease of all members of the methyltransferase complex (METTL3, the only component with catalytic activity; METTL14, which is relevant for substrate recognition, specificity and activity; and WTAP, which stabilizes the complex).…”
Section: Discussionsupporting
confidence: 58%
“…Thus, hypoxia can prime cancer cells for DSBs repair initiation (79). In this sense, it has been recently demonstrated that hypoxia (1% O 2 ) is associated with a higher ɣH2AX foci decay rate and enhanced RAD51 recruitment in irradiated HNSCC cells, suggesting a higher efficacy of HRR under hypoxia in this model (75,80).…”
Section: Repair: the Versatile Impact Of Hypoxia On Dna Damage Repairmentioning
confidence: 90%
“…This potentially primes hypoxic cells for postirradiation DSBs repair initiation. It has also been shown that hypoxia can modify the epigenetic landscape (global loss of H3K27me3 and H3K9me2) by modulating epigenetic enzyme expressions, such as KDM3A and KDM6B and finally promotes DDR activity and radioresistance in HNSCC (80). Moreover, via HIFs, hypoxia can also increase KDM4B expression participating in HRR orchestration (93)(94)(95).…”
Section: Repair: the Versatile Impact Of Hypoxia On Dna Damage Repairmentioning
confidence: 99%
“…Cell viability was evaluated by MTT before the first treatment and 24 h after the final treatment. The CompuSyn software [19] was used to calculate the drug combination index (CI), under the assumption that a value lower than 1 indicates synergistic effects, a value of 1 denotes an additive effect, and a value higher than 1 implies antagonistic effects.…”
Section: Drug Matrix Development and Synergy Assessmentmentioning
confidence: 99%
“…PCa cells (2 × 10 5 for all cell lines) were seeded in flasks and the following day submitted to treatment with the combination of hydralazine and enzalutamide at the concentrations previously calculated. Daily treatments were performed for 72 h. DNA damage was assessed using the protocol described elsewhere [19]. Representative pictures were taken on a microscope (model IX51, Olympus, Tokyo, Japan) and cells were analyzed using the ImageJ software OpenComet Plugin, which measured the tail moment: tail % DNA × means of head × tail distance.…”
Section: Single Cell Gel Electrophoresis (Comet Assay)mentioning
confidence: 99%